2016
DOI: 10.1016/j.str.2016.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding in the Spliceosome via Single α Helices

Abstract: The spliceosomal B complex-specific protein Prp38 forms a complex with the intrinsically unstructured proteins MFAP1 and Snu23. Our binding and crystal structure analyses show that MFAP1 and Snu23 contact Prp38 via ER/K motif-stabilized single α helices, which have previously been recognized only as rigid connectors or force springs between protein domains. A variant of the Prp38-binding single α helix of MFAP1, in which ER/K motifs not involved in Prp38 binding were mutated, was less α-helical in isolation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 57 publications
5
62
0
Order By: Relevance
“…To exclude false positive hits that merely arise from co-occurrence of abundant, highly conserved domains, InParanoid uses a strict cut-off criterion of sequence coverage ≥ 50% and BLAST score ≥ 50. Taking into account the presumably low sequence conservation of MFAP1 due to the predicted structural disorder and the absence of folded protein domains [34], we also performed reciprocal best BLAST hit (RBH) searches of MFAP1 proteins against the same 273 sets of protein-coding genes with relaxed cut-off criteria (BLAST score ≥ 30, E-value ≤ 0.01). The RBH method has a relatively high specificity compared to other ortholog detection methods and its specificity is only marginally affected by changes in cut-off values [39].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To exclude false positive hits that merely arise from co-occurrence of abundant, highly conserved domains, InParanoid uses a strict cut-off criterion of sequence coverage ≥ 50% and BLAST score ≥ 50. Taking into account the presumably low sequence conservation of MFAP1 due to the predicted structural disorder and the absence of folded protein domains [34], we also performed reciprocal best BLAST hit (RBH) searches of MFAP1 proteins against the same 273 sets of protein-coding genes with relaxed cut-off criteria (BLAST score ≥ 30, E-value ≤ 0.01). The RBH method has a relatively high specificity compared to other ortholog detection methods and its specificity is only marginally affected by changes in cut-off values [39].…”
Section: Resultsmentioning
confidence: 99%
“…3a) and of the structurally highly similar Prp38-MFAP1 complex from the thermophilic fungus Chaetomium thermophilum ( ct ; PDB ID: 5F5T, Fig. 3b) together with binding studies of arginine-to-alanine mutants of the first and second arginine (R282, R286), which were sufficient to disrupt Prp38-MFAP1, revealed a RxxxRxxR motif as a key Prp38-binding element of MFAP1 [34]. Strikingly, the C-terminal halves of K. lactis and S. cerevisiae Spp381 contain an identical or slightly modified motif, RxxxRxxR and RxxxRxxK, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a few of these have been characterized experimentally and in detail4569101112. Most recently, it has been shown that in some cases, a region of the SAH can mediate binding to other proteins1314. Thus it is important to understand the underlying stability of these intriguing domains, in order to understand their contribution to protein function.…”
mentioning
confidence: 99%